2021
DOI: 10.1186/s11671-021-03489-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles: A New Approach to Upgrade Cancer Diagnosis and Treatment

Abstract: Traditional cancer therapeutics have been criticized due to various adverse effects and insufficient damage to targeted tumors. The breakthrough of nanoparticles provides a novel approach for upgrading traditional treatments and diagnosis. Actually, nanoparticles can not only solve the shortcomings of traditional cancer diagnosis and treatment, but also create brand-new perspectives and cutting-edge devices for tumor diagnosis and treatment. However, most of the research about nanoparticles stays in vivo and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 134 publications
0
59
0
Order By: Relevance
“…Specifically, anti-tumor research has increasingly utilized nanoparticles (NPs) as carriers due to attractive pharmacokinetic and biodistribution properties, as well as reduced toxicity to the rest of the body. Recent reviews have highlighted various NP strategies aimed at enhancing imaging for diagnosis and drug efficacy for therapy [ 4 , 5 ]. Compared to alternative clinical contrast agents, NPs tend to exhibit higher sensitivity and/or specificity for abnormalities such as tumors due to selective delivery [ 6 ], including preclinical studies that have shown promise for computed tomography, magnetic resonance imaging, ultrasound, and positron emission tomography (see reviews: [ 7 , 8 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, anti-tumor research has increasingly utilized nanoparticles (NPs) as carriers due to attractive pharmacokinetic and biodistribution properties, as well as reduced toxicity to the rest of the body. Recent reviews have highlighted various NP strategies aimed at enhancing imaging for diagnosis and drug efficacy for therapy [ 4 , 5 ]. Compared to alternative clinical contrast agents, NPs tend to exhibit higher sensitivity and/or specificity for abnormalities such as tumors due to selective delivery [ 6 ], including preclinical studies that have shown promise for computed tomography, magnetic resonance imaging, ultrasound, and positron emission tomography (see reviews: [ 7 , 8 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle systems are currently being developed to reduce the adverse effects of standard chemo-and radiotherapeutics. The use of these nanoparticle systems can be beneficial in improving hydrophobic drug delivery and in reducing metabolic drug degradation and targeting specific cells [204,205].…”
Section: Synergistic Effect Of Cap and Nanoparticlesmentioning
confidence: 99%
“…As nanotechnology develops, it is necessary to monitor the immunotoxicity, long-term toxicity, and neurotoxicity of NPs. NPs would be an ideal approach to improve cancer therapy and diagnosis [ 137 ].…”
Section: Perspectivementioning
confidence: 99%